BS EN ISO 20776-2. Clinical laboratory testing and in vitro diagnostic test systems. Susceptibility testing of infectious agents and evaluation of performance of antimicrobial susceptibility test. Part 2. Evaluation of performance of antimicrobial susceptibility test devices against reference broth micro-dilution (30th April 2021) - British Standards Institution,
No abstract available